(untitled) (Medical Forum Monthly, 2020)
Objective: An important polypeptide molecule known as epidermal growth factor (EGF) has significant importance in wound healing and aids in epithelial growth. Its mechanism of action is such that it binds with receptors present on the surface of cell. The main objective of present research is to access, evaluate and make comparison of levels of salivary EGF in individuals having medical conditions like oral gingivitis and advanced periodontitis along with patients with healthy oral cavity conditions. Study Design: Comparative Study Place and Duration of Study: This study was conducted at the Watim Medical and Dental College Rawalpindi September 2019 to January 2020. Materials and Methods: The samples of saliva that were unstipulated gathered from mouth of patients having oral conditions like advanced periodontitis, gingivitis and from individuals with healthy oral conditions at Watim medical and dental college Rawalpindi at September 2019 to January 2020. The clinical parameters that were measured during this case study were bleeding on probing (BOP), plaque index (PI), clinical attachment level (CAL) and probing pocket depth (PPD) with the help of a Williams probe. EGF levels were recorded by using enzyme-linked immune sorbent assay (ELISA). For data analysis and evaluation, One- way ANOVA was used. Results: In Individuals with healthy oral conditions, EGF levels were noteworthy higher (99.00) as compared to patients suffering from gingivitis (62.49). EGF value was still higher in patients with gingivitis as compared to patients with advanced stage periodontitis (37.12) (P<0.001). Conclusion: The decline in mean levels of EGF in individuals suffering from periodontal disease may be due to periodontal diseases.